Dietary intervention in patients with age-related macular degeneration: protocol for a randomised controlled trial. Issue 2 (5th February 2019) - Tang, Diana; Mitchell, Paul; Flood, Victoria; Kifley, Annette; Hayes, Alison; Liew, Gerald; Gopinath, Bamini
Abstract : Introduction: Age-related macular degeneration (AMD) is a leading cause of blindness. After smoking, nutrition is the key modifiable factor in reducing AMD incidence and progression, and no other preventative treatments are currently available. At present, there is an evidence–practice gap of dietary recommendations made by eye care practitioners and those actually practised by patients with AMD. To address this gap, a telephone-delivered dietary intervention tailored to patients with AMD will be piloted. The study aims to improve dietary intake and behaviours in patients with AMD. This type of nutrition-focused healthcare is currently not considered in the long-term management of AMD and represents the first empirical evaluation of a telephone-supported application encouraging adherence to dietary recommendations for AMD. Methods and analysis: 140 participants with AMD will be recruited for this randomised controlled trial. Those lacking English fluency; unwilling to engage in the intervention or provide informed consent were excluded. Following the completion of the baseline questionnaire, participants will be randomised into one of two arms: intervention or wait-list control (70 each in the intervention and control groups). Intervention participants will receive a detailed mail-delivered workbook containing information on healthy eating behaviours that promote optimal macular health, as well as scheduled phone calls over 4 months from an accredited practising dietitian. Descriptive statistics and multivariate stepwise linear regressions analyses will be used to summarise and determine the changes in dietary intakes, respectively. Economic analysis will be conducted to determine intervention feasibility and possibility of a large-scale rollout. Ethics and dissemination: The study was approved by the University of Sydney Human Research Ethics Committee (HREC) (Reference: HREC 2018/219). Study findings will be disseminated via presentations at national/international conferences and peer-reviewed journal articles. Trial registration number: ACTRN12618000527268; Pre-results.